2020
DOI: 10.1111/cpr.12738
|View full text |Cite
|
Sign up to set email alerts
|

SPAG5‐AS1 inhibited autophagy and aggravated apoptosis of podocytes via SPAG5/AKT/mTOR pathway

Abstract: Objectives Podocyte injury is a prediction marker of diabetic nephropathy (DN), and AKT/mTOR pathway–mediated inhibition of autophagy is widely reported to contribute to podocyte damage. Recent study stated that sperm‐associated antigen 5 (SPAG5) activated AKT/mTOR signalling in bladder urothelial carcinoma, indicating SPAG5 might regulate autophagy and play a role in podocyte damage. Materials and methods Apoptosis and autophagy of human podocytes (HPCs) were detected by flow cytometry and immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…Interestingly, the S1 cluster 7 and the S2/3 cluster 3 showed enrichment of "respiratory chain," "mitochondrial inner membrane," and "cytochrome c oxidase activity" (Dataset S2), possibly indicating increased energy demand in these cells. Spag5, encoding a mitotic spindle protein shown to be up-regulated in response to oxidative stress in cancer (26) and in response to high glucose treatment in human podocytes (27), was overrepresented in these clusters as well as in cluster 8 (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the S1 cluster 7 and the S2/3 cluster 3 showed enrichment of "respiratory chain," "mitochondrial inner membrane," and "cytochrome c oxidase activity" (Dataset S2), possibly indicating increased energy demand in these cells. Spag5, encoding a mitotic spindle protein shown to be up-regulated in response to oxidative stress in cancer (26) and in response to high glucose treatment in human podocytes (27), was overrepresented in these clusters as well as in cluster 8 (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…35 Hyperactivity of mTOR and it also regulated the podocyte autophagy deficiency in response to stimuli's. 36,37 In the present sudy, mTOR and ULK1 ser757 phosphorylation were increased, and autophagy decreased by the in stimulation of sPLA2-IB and rapamycin was effective in inhibiting impaired autophagy and podocyte injury evoked by sPLA2-IB. It was found that mTOR phosphorylation and ULK1 ser757 phosphorylation were increased, and autophagy decreased by the in stimulation of sPLA2-IB, which also led to a reduction in the adhesion and an increasing in migratory phenotype of podocytes.…”
Section: Discussionmentioning
confidence: 46%
“…In human podocytes, USP14-mediated deubiquitination and stabilization of SPAG5 contribute to podocyte injury, a clinical predictor of diabetic nephropathy. The USP14/SPAG5-positive-regulatory axis inhibits autophagy and promotes apoptosis by activating AKT/mTOR [ 179 ]. The nickel complex NiPT, which is a proteasomal DUB inhibitor, inhibits USP14 and UCHL5 and promotes autophagy associated with the ER stress/AMPK/mTOR/S6K regulatory axis in lung cancer cells.…”
Section: Dubs Regulating Diverse Rcdmentioning
confidence: 99%